In situ functionalization of scaffolds during extrusion-based 3D plotting using a piezoelectric nanoliter pipette. Issue 1 (January 2017) - Giron, Stefan; Lode, Anja; Gelinsky, Michael
Additive manufacturing techniques can be applied to individually craft medical implants and biomaterial scaffolds. We present the combination of macroscopic scaffold fabrication by strand deposition and high-resolution dosing of liquids using the 'BioScaffolder 2.1' 3D plotter from GeSiM with an integrated piezoelectric nanoliter pipette. A fluorescein solution, used as model substance, was dispensed on calcium phosphate bone cement strands during scaffold production; high reproducibility of the alternating subprocesses was demonstrated. Moreover, the release kinetics of VEGF loaded onto flat calcium phosphate cement substrates was investigated. The presented approach opens up new and exciting possibilities for tissue engineering. Various biological components can be integrated precisely into 3D scaffolds according to a predefined pattern creating tissue equivalents of high complexity.